Using soft X-ray tomography for rapid whole-cell quantitative imaging of SARS-CoV-2-infected cells - Loconte, Valentina; Chen, Jian-Hua; Cortese, Mirko; Ekman, Axel; Le Gros, Mark A.; Larabell, Carolyn; Bartenschlager, Ralf; Weinhardt, Venera (Cell reports. Methods, 2021)
High-resolution and rapid imaging of host cell ultrastructure can generate insights toward viral disease mechanism, for example for a severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. Here, we employ full-rotation soft X-ray tomography (SXT) to examine organelle remodeling induced by SARS-CoV-2 at the whole-cell level with high spatial resolution and throughput. Most of the current SXT systems suffer from a restricted field of view due to use of flat sample supports and artifacts due to missing data. In this approach using cylindrical sample holders, a full-rotation tomogram of human lung epithelial cells is performed in less than 10 min. We demonstrate the potential of SXT imaging by visualizing aggregates of SARS-CoV-2 virions and virus-induced intracellular alterations. This rapid whole-cell imaging approach allows us to visualize the spatiotemporal changes of cellular organelles upon viral infection in a quantitative manner.